2001
DOI: 10.1161/01.hyp.38.3.746
|View full text |Cite
|
Sign up to set email alerts
|

Time-Qualified Reference Values for Ambulatory Blood Pressure Monitoring in Pregnancy

Abstract: Abstract-To recognize the highly statistically significant circadian variability of blood pressure in pregnancy is to admit that the diagnosis of gestational hypertension or preeclampsia should be based not just on whether a casual blood pressure value is too high or too low, but rather on more pertinent questions: How long is blood pressure elevated above a given time-varying threshold? What is the excess blood pressure? When does most of the excess occur? Answers to these questions may be obtained by establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 40 publications
4
25
1
1
Order By: Relevance
“…While all these studies are based on ABPM done for 24 hours only, the most extended conclusion so far is that due to poor results in the diagnostic test based on the BP mean, ABPM does not provide a proper approach for the early identification of preeclampsia, and it should not be used in pregnancy. 11 Against the common approach of relying on the 24-hour mean of ABPM, the combined approach of establishing tolerance intervals for the circadian variability of BP as a function of gestational age 25 and then computing the hyperbaric index (area of BP excess above the upper limit of the tolerance interval) by comparison of any patient's BP profile with those intervals, has been shown to provide high sensitivity and specificity for the early detection of pregnant women who will have subsequent development of gestational hypertension or preeclampsia 12 as well as a proper approach for the prediction of the outcome of pregnancy. 26 Results from this trial on the impact of the duration and frequency of BP sampling on the reproducibility of mean values indicate that parameters calculated from the ABPM profile are much more dependent on duration of sampling than on sampling rate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While all these studies are based on ABPM done for 24 hours only, the most extended conclusion so far is that due to poor results in the diagnostic test based on the BP mean, ABPM does not provide a proper approach for the early identification of preeclampsia, and it should not be used in pregnancy. 11 Against the common approach of relying on the 24-hour mean of ABPM, the combined approach of establishing tolerance intervals for the circadian variability of BP as a function of gestational age 25 and then computing the hyperbaric index (area of BP excess above the upper limit of the tolerance interval) by comparison of any patient's BP profile with those intervals, has been shown to provide high sensitivity and specificity for the early detection of pregnant women who will have subsequent development of gestational hypertension or preeclampsia 12 as well as a proper approach for the prediction of the outcome of pregnancy. 26 Results from this trial on the impact of the duration and frequency of BP sampling on the reproducibility of mean values indicate that parameters calculated from the ABPM profile are much more dependent on duration of sampling than on sampling rate.…”
Section: Discussionmentioning
confidence: 99%
“…23 Although most studies assessing the circadian BP profile have used 24-hour ABPM, as a compromise with practicality, monitoring over at least 48 hours has been shown to present advantages in the analysis of BP variability, 23,39 diagnosis of disease, 12,40 and evaluation of a patient's response to treatment. 39,40 The individualized estimation of rhythm characteristics become more reliable; new end points are obtained, such as the circadian period, which cannot usually be estimated from 24-hour records. 41 Previous findings suggested that ABPM done only for 24 hours may be too short to characterize accurately the features of the day-night variation in BP, including the precise period of that variation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a compromise with practicability, monitoring over at least 48 hour has been shown to present advantages in the analysis of BP variability, 30 diagnosis of disease, 31 and evaluation of a patient's response to treatment. 30,31 Previous findings suggested that ABPM done only for 24 hour may be too short to characterize accurately the features of the day/night variation in BP, including the precise period of that variation. Along these lines, it has been recently demonstrated that, in patients evaluated by ABPM for the first time, there is a highly significant reduction during the second day of monitoring as compared with the first in the diurnal mean of BP.…”
Section: Hermida Et Al Seasonal Variation In Fibrinogenmentioning
confidence: 99%
“…Los individuos con patrón non dipper presentan un perfil de RCV y de lesiones en órganos diana más desfavorable que aquellos que presentan un perfil dipper. El patrón extreme-dipper, favorece la posibilidad que ocurra un ictus hemorrágico [3].…”
Section: Introductionunclassified